Improvement of Water Quality by Hematite Based on River Sand Magnetic Minerals of Lombok Island (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Hematite synthesis has been carried out using magnetic mineral river sand from several areas on the island of Lombok, namely Tanak Beak, Sesao, and Lokoq Rangan. Hematite was then used for metal absorbance in polluted water from the river around the Kebon Kongok landfill. The synthesis method used is coprecipitation. The acid used is HCl with a concentration of 7 M and NH4OH base with a concentration of 25%. Mineral content analysis was carried out using AAS and EDX. Morphological analysis was made using SEM, crystal structure using XRD, and functional group analysis using FTIR, while TDS and water conductivity were measured using a TDS meter. Based on the results of AAS analysis, it appears that the iron content of hematite synthesized from magnetic minerals of tanak beak, sesaot, and lokoq rangan river sand is 8.79%, 10.84% and 9.01% respectively, while based on EDX analysis, it was found to be 70.42%, 77.99% and 72.55%. The particle size of Sesaot iron sand also has the smallest size, at (0.88 ± 0.17) micrometers, while the largest grain size is obtained in the Tanak Beak area, at (1,288 ± 0.23) micrometers. Based on the results of XRD and FTIR analysis, it can be concluded that hematite nanoparticles were successfully synthesized using iron sand based on the Lombok Island River sand. Mn ions absorbed by hematite-based mineralized magnetic river sand from several areas on the island of Lombok, namely Tanak Beak, Sesaot, and Lokoq Rangan, are 9.39%, 27.07% and 13.82% respectively, which is followed by a decrease in TDS and conductivity of the absorbed water. Hematite derived from river sand magnetic minerals can adsorb Mn metal and improve water quality better when compared to hematite based on Tanak Beak and Lokoq Rangan river sand.